Innovative educational apps - Clare, Jayne (Base Diseño e Innovación, 2016)
An iPad is only as GOOD as the Content On it. Content, content, content! Any app that stands the test of time does so because it has relevant and lasting content. Case in point, we (TWA) download many, many apps…. what stays on our iPad’s? Only the best of the bunch. Your iPad is only as good as the content on it.